Study of residual soil slope stability with the application of horizontal drainage - Md. Rahim, Mohd Syazwan; Mohd Taib, Aizat; Abd. Rahman, Norinah; Mohd Fauzi, Nurul Hidayatul Akhmal; Ramli, Ahmad Bukhari (2021)
This study determines the effectiveness of horizontal drains on a slope which refers to a landslide at Putrajaya, Malaysia, in 2007. The incident buried 27 cars, and about 1200 people were transferred to a safe place. The main cause was identified as continuous and heavy rainfall. In Malaysia, abundant rainfall is common during the wet season. Therefore, one of the remedial measures to improve slope stability is applying horizontal drain to flush out rising groundwater and increase soil strength. In this study, the finite element method package, Plaxis, is used to analyze the slope stability changes in terms of the factor of safety (FOS). The simulation of slope behavior includes the horizontal drain conditions in lowering the groundwater level based on three parameters: the heights, appropriate depth, and inclination angle. The horizontal drains are installed at four different heights of 1 m, 2 m, 8 m, and 28 m from the toe of the slope. Based on the results, the horizontal drain is most efficient to be installed with 15 m long and zero degrees angle at the height of 1 m from the toe of the slope. At 2 m height, the drain should be installed with 26 m long and an angle of 1.8 degrees, and at 8 m height, the drain should be installed with 12 m long and an angle of 4.8 degrees. Moreover, at 28 m, the horizontal drain should be installed 20 m long and at an angle of 8.5 degrees. Therefore, this paper highlights the exceedingly appropriate design of horizontal drains at different heights, lengths, and tilt angles along the slope surface.